Dysregulation of LncRNAs in Placenta and Pathogenesis of Preeclampsia - Song, Xuejing; Luo, Xiucui; Gao, Quansheng; Wang, Yuhuan; Gao, Qing; Long, Wei (Current drug targets, 2017)
Preeclampsia, a gestational disease characterized by hypertension and proteinuria twenty weeks into pregnancy, is one of the leading causes of fetal and maternal mortality. Although multiple genetic and environmental factors are found to be related to the preeclampsia risk, the pathogenic pathways remain largely undefined. The placenta plays a critical role in the fetal development by carrying out the barrier, fetal-maternal exchange, and endocrine functions during pregnancy. Accumulated data indicated that the expression of multiple long noncoding RNA (LncRNA) is dysregulated in preeclamptic placentas. Moreover, manipulation of LncRNA expression led to functional alterations in trophoblast cell cultures, including changes in proliferation, differentiation, apoptosis, and migration. This article reviews published data on this subject and provides detailed information on the regulation and function of LncRNAs IGF2/H19, MEG3, SPRY4-IT1, HOTAIR, MALAT1, and FLT1P1 and CEACAMP8 in placental trophoblasts. The potential mechanisms underlying the action of these LncRNAs are also discussed to facilitate a better understanding on the potential role of these LncRNAs for the pathogenesis of preeclampsia. It is elaborated that some lncRNAs probably contribute to the pathogenesis of preeclampsia through methylation, Notch-EGFL7 signaling pathway and Wnt/β-catenin pathway.